Centrifuge Model Test on the Settlement of Valley-Type Loess Filled after Construction and Subjected to Rainfall Infiltration - Jiwen Zhang; Jie Cao; Bo Li; Kunye Zhou; Xilin Lü (Advances in Civil Engineering)
With the rapid development of infrastructure construction in western China where hilly and gully areas are distributed, there are lots of large-scale filling engineering in recent years. In the area where collapsible loess is widely distributed, it is inevitable to use loess as filling material. Considering the collapsibility of loess, centrifuge model tests were conducted to study the settlement of loess fill in a valley after construction and subjected to rainfall infiltration. To provide a comparison, a centrifuge model test of loess filling body on a flat ground was conducted, and results showed that the settlement of loess fill during the construction stage is larger than the one at the postconstruction stage, and the unloading rebound deformation caused by decreasing gravity is about 15% of the deformation induced by increasing gravity. Two centrifuge model tests were conducted to study the settlement of the loess filling body in a valley; the varying characteristics of settlement and earth pressure with time at the postconstruction stage and subjected to rainfall infiltration were investigated. Differential settlement in the ground surface was observed at the postconstruction stage, and it was found to become very small under the rainfall infiltration condition. Comparison of the test results showed that insufficient compaction in the lower part of the filling body significantly increases the ground settlement at the postconstruction stage.